2019
DOI: 10.1371/journal.pone.0220507
|View full text |Cite|
|
Sign up to set email alerts
|

Smoking, alcohol use disorder and tuberculosis treatment outcomes: A dual co-morbidity burden that cannot be ignored

Abstract: Background More than 20% of tuberculosis (TB) disease worldwide may be attributable to smoking and alcohol abuse. India is the second largest consumer of tobacco products, a major consumer of alcohol particularly among males, and has the highest burden of TB globally. The impact of increasing tobacco dose, relevance of alcohol misuse and past versus current or never smoking status on TB treatment outcomes remain inadequately defined. Methods We conducted a multi-centric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 39 publications
5
46
0
2
Order By: Relevance
“…65% of the patients were found to be male in Thomas et al study. 13 Thomas et al found 28% of their study group was smokers.…”
Section: Discussionmentioning
confidence: 89%
“…65% of the patients were found to be male in Thomas et al study. 13 Thomas et al found 28% of their study group was smokers.…”
Section: Discussionmentioning
confidence: 89%
“…Considering the regional setting where the included studies were done; six (17,25,35,37,38,48), ve (41,46,47,49,50) and another ve studies were from Russia, South Africa (33,34,51,52,54) and Ethiopia (33,34,51,52,54) respectively. The remaining studies were from United States (US) (36,39), Estonia (42,43), India (14,44,53), Thailand (45), Nigeria (40), Botswana (15) and Zambia (11). Most of the studies in the present analysis were Cohort (25,35,38,41,45,47,49,(52)(53)(54) and cross-sectional (11,14,17,33,34,36,37,42,…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
“…The remaining studies were from United States (US) (36,39), Estonia (42,43), India (14,44,53), Thailand (45), Nigeria (40), Botswana (15) and Zambia (11). Most of the studies in the present analysis were Cohort (25,35,38,41,45,47,49,(52)(53)(54) and cross-sectional (11,14,17,33,34,36,37,42,44,46,50,51).…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…В многоцентровом проспективном когортном исследовании взрослых пациентов с туберкулезом легких было продемонстрировано, что риск рецидива ТБ среди курящих был выше в 2,94 раза (RR=2,94; 95% ДИ 1,30-6,67; p=0,010), а смертность -в 2,59 раза по сравнению с некурящими (RR=2,59; 95% ДИ 1,29-5,18; р=0,007). Кроме того, злоупотребление алкоголем наряду с курением увеличивает риски неблагоприятных результатов лечения в 3,58 раза (RR=3,58; 95% ДИ 1,89-6,76; р<0,001) [5].…”
Section: Introductionunclassified